2022
DOI: 10.1029/2021gl096489
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Predictability of Lightning Over the Global Hotspot Regions

Abstract: Lightning is one of the most powerful, all-pervasive atmospheric hazards. Lightning fatalities over India (Mahapatra et al., 2018; Accidental Deaths and Suicides in India (ADSI) Report, Govt. of India) result in severe societal and economic consequences as lightning affects aviation, telecommunication, agriculture, electricity, and many more sectors. Keeping in mind the lifetime injuries, physiological trauma, disabilities that are caused by lightning (e.g., Mahapatra et al., 2018;Singh and Singh, 2015), an ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Hence, the strong vertical updraft lofts a large quantity of graupel particles at a higher altitude. The short‐lived and large‐scale organized convection during pre‐monsoon and monsoon, respectively, are also responsible for this region's high lightning flash rate (Kamra & Ramesh Kumar, 2021; Mallick et al., 2022). The high‐value of CAPE plays an important role in generating high lightning producing intense thunderstorms over this region in monsoon (Murugavel et al., 2014), which may produce high IC flash rates and favors a very high Z ratio. The northeastern part of India (Region 3) shows a low value of Z ratios in monsoon (around 0.5–3.5) and pre‐monsoon (around 1.5–4.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the strong vertical updraft lofts a large quantity of graupel particles at a higher altitude. The short‐lived and large‐scale organized convection during pre‐monsoon and monsoon, respectively, are also responsible for this region's high lightning flash rate (Kamra & Ramesh Kumar, 2021; Mallick et al., 2022). The high‐value of CAPE plays an important role in generating high lightning producing intense thunderstorms over this region in monsoon (Murugavel et al., 2014), which may produce high IC flash rates and favors a very high Z ratio. The northeastern part of India (Region 3) shows a low value of Z ratios in monsoon (around 0.5–3.5) and pre‐monsoon (around 1.5–4.5).…”
Section: Resultsmentioning
confidence: 99%
“…However, limited studies assess the Z ratio and its spatial and seasonal variability over the Indian subcontinent. Moreover, recent studies (Mallick et al., 2022) have shown that lightning‐related loss of human lives and loss of properties primarily happens during the monsoon season in the Indian region. Moreover, the higher orographic Himalayan region in the northern belt of the Indian region also influences the intense lightning activity seasonally.…”
Section: Introductionmentioning
confidence: 99%
“…Girishkumar and Ravichandran (2012) have shown the influence of ENSO on tropical cyclone (TC) activity (frequency, genesis location and intensity) in the Bay of Bengal (BoB). It is also shown that ENSO has the strongest relationship with lightning activity (Dowdy, 2016; Mallick et al, 2022; Muñoz et al, 2016). During synoptic‐scale events (i.e., lows, depression, cyclones, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Both the large and short scale climatic drivers were reported to have visible impact on lightning over north western Venezuela which happens to have the highest annual lightning rate (Munoz et al ., 2016). Particularly over lightning hot‐spots like India, the lightning activity has been reported to be very well predictable by slowly varying global predictors (Mallick et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%